Phospholipase A and acyltransferase 4/retinoic acid receptor responder 3 at the intersection of tumor suppression and pathogen restriction - Zhao, Jian-Yong; Yuan, Xiang-Kun; Luo, Rui-Zhen; Wang, Li-Xin; Gu, Wei; Yamane, Daisuke; Feng, Hui (Frontiers in Immunology, 2023)
Phospholipase A and acyltransferase (PLAAT) 4/retinoic acid receptor responder 3 (RARRES3) is a class II tumor suppressor with phospholipid metabolizing abilities. Two decades of research have revealed the complexity of its function and regulatory roles in suppressing tumorigenesis. However, more recent findings have suggested PLAAT4 as a key anti-microbial effector enzyme acting downstream of interferon regulatory factor 1 (IRF1) and interferons (IFNs), favoring a protection from viral and parasite infections. Unveiling molecular mechanisms of its action may open new therapeutic avenues for the treatment of cancer and infectious diseases.